AKTIVITAS ANTIBAKTERI NISIN DALAM MIKROSFER MATRIKS ALGINAT-GELATIN (2,5:0,5)% DALAM MEDIA DAPAR SITRAT pH 6,0 (Bakteri Uji Staphylococcus aureus ATCC 6538) - INDAH LU’LU’ATIN MANTSURO, 051311133209 (2017)
The aim of this study is to analyze antibacterial activity profile of nisin in microsphere using alginate-gelatin (2.5:0.5)% as matrix. Antibacterial activity test completed by diffusion method using Staphylococcus aureus ATCC 6538 as bacteria experiment. Antibacterial activity of nisin in microsphere using citric buffer pH 6.0 + 0.05 as medium shown by inhibitory zone. By these results, we had antibacterial activity profile of nisin in microsphere. The inhibitory zone was presented to a linear regression equation y = 5.7859 x + 8.5203. The results had an antibacterial activity equivalence of nisin in microsphere to gentamicin sulfate against Staphylococcus aureus ATCC 6538. The results in 6 hours were 2.79 ppm, 3.87 ppm, 3.99 ppm, 5.56 ppm, 6.11 ppm and 6.49 ppm.